Body adiposity index to analyze the percentage of fat in young men aged between 7 and 17 years. Issue 2 (24th March 2021) - de Macêdo Cesário, Tatianny; de Almeida‐Neto, Paulo Francisco; de Matos, Dihogo Gama; Wells, Jonathan; Aidar, Felipe J.; da Costa, Roberto Fernandes; de Araújo Tinoco Cabral, Breno Guilherme
Abstract: Background: The body adiposity index (BAI), uses anthropometry to estimate percent body fat (%F). However, previous studies have shown that the BAI has limited accuracy for children and adolescents. Objective: We propose to develop and validate an adjusted BAI for use in male children and adolescents from 7 to 17 years of age. Methods: The sample consisted of 141 physically active male children and adolescents (age: 12.5 ± 2.14). The %F was determined by X‐ray dual energy absorptometry equipment (DXA) as the standard method and by BAI, using an equation that uses height and hip circumference. Arithmetic modeling was used to adjust the structure of the BAI mathematical model. Results: The BAI arithmetic adjustment was successful, resulting in the mathematical model named in the present study of adjusted body adiposity index (BAIADJ ). BAI and BAIADJ correlated with DXA ( r ≤ .70, p < .001). Regression analyzes indicate that, BAI (CI 95% β: [1.35; 1.90], p < .0001) and BAIADJ (CI 95% β: [1.40; 1.90], p < .0001) have the potential to estimate %F. BAI pointed out a difference in relation to DXA ( p = .04). While there was no difference between BAIADJ and DXA ( p = .1). There was a proportion bias of 13.2% for BAI ( p < .05), but not for BAIADJ ( p > .05). Conclusion: The adjusted model of the body adiposity index proves to be an effective tool for the analysis of the fat percentage in young males. In addition, it demonstrated significant degrees of agreement and validity in relation to DXA.